SIFAT-SIFAT TANAH DAN AIR YANG TERPENGARUH TSUNAMI DI KECAMATAN LHOONG KABUPATEN ACEH BESAR - Hairul Basri; Syakur Syakur; Alfian Rusdi (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2011)
ABSTRACT The aims of the research were to evaluate soil characteristics, to study land suitability and to propose recommendation of land use and rehabilitation of the tsunami affected agricultural area in Lhoong Sub-District. The result showed that soil textures were varied from very coarse at the area near the coastline to rather fine at the area far from the coast. The soil structures of topsoil were generally plate and blocky, and at subsoil generally massive. The quality of irrigation water in Sub District of Lhoong was still suitable for crops. The pH of water was neutral and low in salinity (0, 4 mS cm-1). The recommendations for land of class A were (1) cleaning and repairing of irrigation and drainage channel, (2) leaching of salinity in topsoil from soil profile by flooding method (irrigation basin) or furrow irrigation, (3) making the ditches for cultivation in managing the excess of salinity, (4) establishing ditches for paddy, and (5) requiring a specified amount of water for the leaching processes and the amount of water required for crops. The recommendation for land class B were (1) cleaning and repairing of irrigation and drainage channel, (2) removing the sediment above the topsoil, (3) leaching the salt from topsoil passing soil profile by irrigation water, (4) constructing ditches for cultivation in managing the excess of salinity.